Efficacy of cancer vaccines in selected gynaecological breast and ovarian cancers: A 20-year systematic review and meta-analysis. (January 2021) - Dafni, U.; Martín-Lluesma, S.; Balint, K.; Tsourti, Z.; Vervita, K.; Chenal, J.; Coukos, G.; Zaman, K.; Sarivalasis, A.; Kandalaft, L.E.
Abstract: Background: Therapeutic cancer vaccination is an area of interest, even though promising efficacy has not been demonstrated so far. Design: A systematic review and meta-analysis was conducted to evaluate vaccines' efficacy on breast cancer (BC) and ovarian cancer (OC) patients. Our search was based on the PubMed electronic database, from 1st January 2000 to 4th February 2020. Objective: response rate (ORR) was the primary end-point of interest, while progression-free survival (PFS), overall survival (OS) and toxicity were secondary end-points. Analysis was performed separately for BC and OC patients. Pooled ORRs were estimated by fixed or random effects models, depending on the detected degree of heterogeneity, for all studies with more than five patients. Subgroup analyses by vaccine type and treatment schema as well as sensitivity analyses, were implemented. Results: Among 315 articles initially identified, 67 were eligible for our meta-analysis (BC: 46, 1698 patients; OC: 32, 426 patients; where both BC/OC in 11). Dendritic-cell and peptide vaccines were found in more studies, 6/10 BC and 10/13 OC studies, respectively. In our primary BC analysis (21 studies; 428 patients), the pooled ORR estimate was 9% (95%CI[5%, 13%]). The primary OC analysis (12 studies; 182 patients), yielded pooled ORR estimate of 4% (95%CI[1%, 7%]). Similar were the results derived in sensitivity analyses. No statistically significant differences were detected by vaccine type or treatment schema. Median PFS was 2.6 months (95% confidence interval (CI)[1.9, 2.9]) and 13.0 months (95%CI[8.5, 16.3]) for BC and OC respectively, while corresponding median OS was 24.8 months (95%CI[15.0, 46.0]) and 39.0 months (95%CI[31.0, 49.0]). In almost all cases, the observed toxicity was only moderate. Conclusion: Despite their modest results in terms of ORR, therapeutic vaccines in the last 20 years display relatively long survival rates and low toxicity. Since a plethora of different approaches have been tested, a better understanding of the underlying mechanisms is needed in order to further improve vaccine efficacy. Highlights: First meta-analysis in therapeutic vaccines for breast/ovarian cancer. Many alternative approaches have been tested in heterogeneous cohorts. Most patients included in these studies were advanced and heavily pre-treated ones. Response results are only modest, but survival rates are long and toxicity low. More studies are needed to evaluate basic mechanisms and improve vaccines' efficacy.